JEE-Mains 2015 (3/30)

Algebra Level 3

Let α \alpha and β \beta be the roots of equation x 2 6 x 2 = 0 x^2-6x-2=0 .

If a n = α n β n a_n=\alpha^n-\beta^n for n 1 , n \geq 1, then the value of a 10 2 a 8 2 a 9 \dfrac{a_{10}-2a_8}{2a_9} is equal to __________ . \text{\_\_\_\_\_\_\_\_\_\_}.

-6 -3 3 6

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Vishnu Bhagyanath
Jun 15, 2015

From the equation, product of roots is 2 -2 a 10 2 ( a 8 ) 2 ( a 9 ) = ( α 10 β 10 ) ( α β ) ( α 8 β 8 ) 2 × ( α 9 β 9 ) \frac{a_{10} - 2(a_8)}{2(a_9)} = \frac{(\alpha ^{10} - \beta ^{10}) - (-\alpha\beta)(\alpha ^8- \beta ^8)}{2 \times (\alpha ^9 - \beta ^9)} Opening the bracket and taking common terms, α 9 ( α + β ) β 9 ( α + β ) 2 × ( α 9 β 9 ) \frac{\alpha ^9(\alpha+\beta) - \beta^9(\alpha + \beta) }{2 \times (\alpha ^9 - \beta ^9)} α + β 2 \frac{\alpha + \beta}{2} From the equation, sum of roots is 6 6 . Therefore the answer is 3 3

Thank you very much......you saved me hundreds....

Sai Ram - 4 years, 7 months ago

....I'm sorry for my ignorance, but I don't know why it is positive.

Karen Sarai Morales Montiel - 3 years, 4 months ago
Sandeep Rathod
Jun 17, 2015

α 2 6 α 2 = 0 \alpha^2 - 6\alpha - 2 =0

Multiplying by α 8 \alpha^{8}

α 10 6 α 9 2 α 8 = 0 \alpha^{10} - 6\alpha^{9} -2\alpha^{8} = 0

Similarly

β 10 6 β 9 2 β 2 = 0 \beta^{10} - 6\beta^{9} -2 \beta^{2} = 0

Adding,

α 10 + β 10 2 α 8 β 8 = 6 ( α 9 + β 9 ) \alpha^{10} + \beta^{10} - 2\alpha^{8} - \beta^{8} = 6( \alpha^{9} + \beta^{9})

a 10 2 a 8 2 a 9 = 3 \dfrac{a_{10}-2a_8}{2a_9} = 3

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...